2020
DOI: 10.1186/s12891-020-03762-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery for intra-articular calcaneus fractures: a 9-year, single-center, retrospective study of a standardized technique using a 2-point distractor

Abstract: Background A fracture of the calcaneus can be a painful and disabling injury. Treatment modalities may be conservative or operative. Surgical treatment strategies include open reduction and internal fixation (ORIF) techniques, as well as a variety of minimally invasive methods. The aim of this study was to evaluate the treatment options and post-treatment complication rates for intra-articular calcaneal fractures at the Traumacenter Linz over a 9-year period. Methods All patients with calcaneal fractures trea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In recent years, with the growth of the construction industry, incidents involving falls from signi cant heights have been on the rise, leading to a notable increase in severe, comminuted calcaneal fractures, including Sanders IV type fractures [6]. The calcaneus, a critical weight-bearing structure for upright ambulation, exhibits a higher morbidity rate when a icted with Sanders IV type fractures [7]. However, there remains a lack of consensus in the clinical community regarding the optimal treatment approach for Sanders IV calcaneal fractures [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the growth of the construction industry, incidents involving falls from signi cant heights have been on the rise, leading to a notable increase in severe, comminuted calcaneal fractures, including Sanders IV type fractures [6]. The calcaneus, a critical weight-bearing structure for upright ambulation, exhibits a higher morbidity rate when a icted with Sanders IV type fractures [7]. However, there remains a lack of consensus in the clinical community regarding the optimal treatment approach for Sanders IV calcaneal fractures [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Advantages of Guided Distractor Besch et al 21 reported excellent results using external fixators for calcaneal fractures with severe soft tissue injuries. Rodemund et al 8 reported the use of a spreader in the lateral position, but its limitations include the need to perform it under a specially designed stent. To achieve a good reduction effect and soft tissue protection, we began to use the distractor in the medial foot to correct shortening varus deformity.…”
Section: Advantages Of "Out-in" Positionmentioning
confidence: 99%
“…6,7 However, indirect repositioning such as prying is usually performed for medial wall repositioning, which may not restore the normal length, resulting in an inversion shortening deformity. Although there are clinical reports of good results using temporary external fixation bracing and repositioning in the medial position, 8 there may be shortcomings such as occlusion of fluoroscopy and obstruction of internal fixation placement. In addition, skin necrosis rates of this technique have been reported to be as high as 13.8%-29%.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum calcaneal lateral approach is 5 cm proximal and in line with the base of the fifth metatarsal to provide lifting the collapsed thalamic surface, followed by introduction of percutaneous K. wires and screws under roentgenographic guidance ( Fig. 1 ) ( 13 ). Stabilization of the fracture is achieved following restoration of the thalamic surface with a steinmann nail, K. brooches or percutaneous screws.…”
Section: Introductionmentioning
confidence: 99%